The effect of aging, nutrition, and exercise during HIV infection - Gabriel Somarriba (Dove Medical Press, 2010)
Gabriel Somarriba, Daniela Neri, Natasha Schaefer, Tracie L MillerDivision of Pediatric Clinical Research, Department of Pediatrics, Miller School of Medicine, University of Miami, Miami, Florida, USAAbstract: Medical advances continue to change the face of human immunodeficiency virus–acquired immunodeficiency syndrome (HIV/AIDS). As life expectancy increases, the number of people living with HIV rises, presenting new challenges for the management of a chronic condition. Aging, nutrition, and physical activity can influence outcomes in other chronic conditions, and emerging data show that each of these factors can impact viral replication and the immune system in HIV. HIV infection results in a decline of the immune system through the depletion of CD4+ T cells. From initial infection, viral replication is a continuous phenomenon. Immunosenescence, a hallmark of aging, results in an increased susceptibility to infections secondary to a delayed immune response, and this phenomenon may be increased in HIV-infected patients. Optimal nutrition is an important adjunct in the clinical care of patients with HIV. Nutritional interventions may improve the quality and span of life and symptom management, support the effectiveness of medications, and improve the patient’s resistance to infections and other disease complications by altering immunity. Moderate physical activity can improve many immune parameters, reduce the risk of acute infection, and combat metabolic abnormalities. As people with HIV age, alternative therapies such as nutrition and physical activity may complement medical management.Keywords: HIV replication, aging, diet, nutrition, exercise, immunity